Dampak Sosial Ekonomi Relokasi Pedagang Kaki Lima di Kecamatan Buduran Kabupaten Sidoarjo - Mochammad Aringga Prasetya; Luluk Fauziah (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2016)
The purpose of this study was to describe the process of relocating street vendors, socio-economic impacts of the relocation of street vendors, enabling and inhibiting factors in the relocation of street vendors Buduran Sidoarjo District flyover. The method used is descriptive qualitative. The key informants in this study is a cooperative trade field staff, SMEs, Trade and Industry Sidoarjo. With the technique of collecting data through interviews, observation and documentation and then analyzed through the stages of data collection, data reduction, data presentation and conclusion. The results showed that the process of relocating street vendors are not in accordance with the stages of the relocation as stipulated in the Regulation of Home Affairs Number 41 Year 2012 which begins from the stage of data collection by the two surveys and registration of street vendors, determining the location of street vendors, transfer and removal of the location of street vendors, for the rejuvenation of the location of street vendors. Relocation was finally done by the Department of Hygiene and Sidoarjo Regency which take discretionary acts such policies. The social impact of the relocation of street vendors in the area overpass Buduran district, in terms of comfort PKL more comfortable. But in terms of security is still not fully awake. PKL majority income declined due to the lack of empowerment of government. The government also has obstacles in the relocation of street vendors because of the limited land available as well as street vendors mindset still comfortable selling on the shoulder of the road because there is no money to rent a place.